Improving effectiveness and outcomes for the poor in health, nutrition, and population : an evaluation of World Bank Group support since 1997. (Independent evaluation studies., 2009)
This study evaluates the effectiveness of the World Bank Group's support for health, nutrition, and population (HNP) in developing countries from 1997 to 2008 - totaling more than 17 billion - and distills lessons for greater impact in the future. It finds that the Bank Group now funds a smaller share of global support for HNP than a decade ago, but its support remains substantial and adds considerable value. About two-thirds of the Bank's HNP support has had satisfactory outcomes, often in difficult environments.